Kerouac in ecstasy shamanic expression in the writings - Bierowski, Thomas R., 1962- (McFarland & Co., Publishers, 2011)
"This critical text considers Jack Kerouac as writer-shaman, exploring the content and ecstatic technique of the novels and two experimental volumes that represent critical phases of his development. Author Thomas Bierowski also examines the reception of Kerouac's work"--Provided by publisher.